Optimizing Diffusion Imaging Protocols for Structural Connectomics in Mouse Models of Neurological Conditions - Anderson, Robert J.; Long, Christopher M.; Calabrese, Evan D.; Robertson, Scott H.; Johnson, G. Allan; Cofer, Gary P.; O'Brien, Richard J.; Badea, Alexandra (Frontiers in Physics, 2020)
Network approaches provide sensitive biomarkers for neurological conditions, such as Alzheimer’s disease (AD). Mouse models can help advance our understanding of underlying pathologies, by dissecting vulnerable circuits. While the mouse brain contains less white matter compared to the human brain, axonal diameters compare relatively well (e.g. ~0.6 µm in the mouse and ~0.65-1.05 µm in the human corpus callosum). This makes the mouse an attractive test bed for novel diffusion models and imaging protocols. Remaining questions on the accuracy and uncertainty of connectomes have prompted us to evaluate diffusion imaging protocols with various spatial and angular resolutions. We have derived structural connectomes by extracting gradient subsets from a high spatial, high angular resolution diffusion acquisition (120 directions, 43 µm size voxels). We have simulated protocols with 12, 15, 20, 30, 45, 60, 80, 100, and 120 angles; and at 43, 86 or 172 µm voxel sizes. The rotational stability of these schemes increased with angular resolution. The minimum condition number was achieved for 120 directions, followed by 60 and 45 directions. The percentage of voxels containing 1 dyad was exceeded by those with 2 dyads after 45 directions, and for the highest spatial resolution protocols. For the 86 or 172 µm resolutions these ratios converged towards 55% for 1, and 39% for 2 dyads respectively, with less than 7% from voxels with 3 dyads. Tractography errors, estimated through dyad dispersion, decreased most with angular resolution. Spatial resolution effects became noticeable at 172 µm. Smaller tracts, e.g. the fornix, were affected more than larger ones, e.g. fimbria. We observed an inflection point for 45 directions, and an asymptotic behavior after 60 directions, corresponding to similar projection density maps. Spatially downsampling to 86 µm, while maintaining the angular resolution achieved a subgraph similarity of 96% relative to the reference. Using 60 directions with 86 or 172 µm voxels resulted in 94% similarity. Node similarity metrics indicated that major white matter tracts were more robust to downsampling relative to cortical regions. Our study provides guidelines for new protocols in mouse models of neurological conditions, so as to achieve similar connectomes, while increasing efficiency.